Non-destructive quality estimation and internal pigmentation discrimination of ‘Sanguinelli’ blood oranges using hyperspectral imaging - Salvador Castillo-Girones; María E. García-Pastor; María Serrano; Daniel Valero; Sergio Cubero; Salvador Castillo (Food Control, 2026)

Material flow and sustainable utilization of end-of-life motorcycles under Taiwan’s vehicle electrification policy - Hsin-Tien Lin; Kuo-Che Weng; Daniel Sebastián Castillo-Castro (Waste Management, 2026)

Experimental investigation of a dual-spar floating offshore wind farm with a shared mooring line: Extended campaign with multiple wave conditions, improved instrumentation, and reduced mooring stiffness - Daniel Ponce-Matilla; Antonio Medina-Manuel; Amalia Castillo-Martinez; Connor Sterling; Julio Oria-Escudero; Leandro Saavedra Ynocente; Adolfo Marón; Sergio Amores-Carballo; Tomas Lopez-Olocco; Javier Moreno-Robles; Antonio Souto-Iglesias (Engineering Structures, 2026)

Spatial Partitioning of Microbial Functional Potential Suggests Complex Nitrogen Cycling in a Subterranean Estuary - Daniel Romano‐Gude; Nestor Arandia‐Gorostidi; Catalina Mena; Marc Diego‐Feliu; Bella Almillategui; Anna J. Székely; Stefan Bertilsson; Andrea G. Bravo; Jesus Carrera; Cristina Romera‐Castillo; Albert Folch; Jordi Garcia‐Orellana; et al. (Environmental Microbiology, 2026)
Subterranean estuaries (STEs) are key bioreactors regulating the quantity and chemical composition of groundwater‐derived nitrogen (N) reaching coastal ecosystems. Yet, the microbial controls on N‐cycling within these groundwater–seawater mixing zones remain poorly understood. We investigated the spatio‐temporal variations in microbial communities and their N‐cycling potential within an alluvial Mediterranean STE with high N concentration. We explored changes in microbial abundance, heterotrophic activity, taxonomic composition, and the abundance of N‐cycling genes across groundwater samples collected at several depths and distances from the shoreline in winter and summer. Microbial abundance, activity, and diversity varied strongly across hydrochemical zones according to physicochemistry and aquifer depth but showed limited seasonality. Functional predictions suggested a complex, spatially structured suite of N pathways encoded by diverse taxa occupying different STE zones, and quantitative‐PCR revealed niche partitioning between ammonia‐oxidizing archaea, prevalent in fresh‐groundwater, and bacterial denitrifiers enriched in deep‐saline layers. Multiple linear model predictions showed a stronger fit for NO 2 − and NH 4 + concentrations when using microbial properties than when using environmental variables, highlighting their importance for understanding N cycling in STEs. Our results suggest that the functional potential of the STE microbiome is complex and spatially structured across hydrochemical zones, explaining spatial variations in STE N‐cycling.

Holocene biodiversity of marine invertebrates on the south-central Andean coast (14°–26° S): A large-scale archaeological assessment - Daniel Hernández Castillo; Laura Olguín; Jimena Valenzuela; Luna Vásquez; Carola Flores Fernandez (Quaternary International, 2026)

Middle and Late Holocene occupation of a coastal cave in the temperate evergreen rainforest of South-Central Chile, Southwestern South America (40°S) - Simón Sierralta Navarro; Constanza Cortés Rodríguez; Marcelo Godoy Gallardo; Evelyn Munzenmayer Hernández; Daniel Hernández Castillo; Carolina Lagos-Carrasco; Eduardo Silva Carrasco; Claudia Guerra Sánchez; Leonor Adán Alfaro (Quaternary International, 2026)

Optimization of controlled germination conditions enhances bioactive compounds and antioxidant capacity and improves protein digestibility of Andean lupin (Lupinus mutabilis Sweet) - Luz María Paucar-Menacho; Alicia Lavado-Cruz; Anggie Verona-Ruiz; Wilson Daniel Simpalo-Lopez; Williams Esteward Castillo-Martínez; Grimaldo Wilfredo Quispe-Santivañez; John Gonzales-Capcha; Nathalia de Andrade Neves; Marcio Schmiele (Food Bioscience, 2026)

blaNDM-5-positive and mcr-9-carrying Escherichia coli lineages in wild Andean condors feeding at landfills in South America - Danny Fuentes-Castillo; Víctor Escobar-Gimpel; Bruna Fuga; Herrison Fontana; Fábio P. Sellera; Valentina Aravena-Ramírez; Fernanda Esposito; Daniela Castro-Tardón; Elder Sano; Montserrat del Campo-Parod; Jorge Barraza-Schulmeyer; Paula Aravena; et al. (Veterinary Microbiology, 2026)

A conceptual framework for mineral supply chain traceability: Enabling conditions and core dimensions - Paulina Fernández; Michael Tost; Daniel Monfort Climent; Thania Nowaz; Emilio Castillo (The Extractive Industries and Society, 2026)

Vaccine strategies for cancer prevention in Lynch syndrome: the potential of dendritic cell-based therapy - Romy N. Kuipers; Mark A. J. Gorris; Cristina Bayó; Tom Hofland; Daniel Benítez Ribas; Georgina Flórez Grau; Nicoline Hoogerbrugge; Joaquin Castillo; Francesc Balaguer; Tanya M. Bisseling; Gerty Schreibelt; I. Jolanda M. de Vries (Familial Cancer, 2026)
Cancer vaccines offer a promising strategy for cancer prevention, particularly in hereditary cancer syndromes such as Lynch syndrome (LS). LS is characterized by a high lifetime risk of developing various malignancies due to defects in DNA mismatch repair, leading to an accumulation of mutations, particularly frameshift insertion/deletions (indels) within microsatellite loci. These indels create shared tumour-specific neoantigens, which are unique to LS and can be recognized by the immune system and trigger cancer cell killing. Importantly, these neoantigens are also present in precancerous lesions, making LS an ideal target for immune-interception strategies aimed at prevention. Over the years, a variety of vaccine designs targeting different antigens along with a range of delivery platforms have been explored for different types of tumours, each with its own advantages and limitations. In this review, we provide an overview of the key antigens and delivery platforms used in cancer preventive vaccine development for LS, evaluate their limited clinical outcomes to date, and explore the future directions of preventive vaccine immunotherapy. A particular focus is placed on the promising potential of dendritic cell vaccination therapy as a future approach in this field.

The threat of multidrug-resistant microorganisms: active surveillance of key antimicrobial resistant pathogens in 2025 - a report from the INVIFAR network - Adrián Martínez-Meléndez; Elvira Garza-González; María del Rosario Vázquez-Larios; Melissa Garibaldi-Rojas; Bernardo Alfonso Martinez-Guerra; Christian Daniel Mireles-Davalos; Samuel Pavel Escalante-Armenta; José Manuel Feliciano-Guzmán; Daniel Romero-Romero; Maria del Consuelo Velazquez-Acosta; Sandra Quintana-Ponce; Shaúl Ariel Navarro-Lara; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2026)
Purpose Systematic collection and analysis of antimicrobial resistance data from key bacterial pathogens is essential to contribute to control antimicrobial resistance (AMR). The aim of this work was to survey the drug resistance on clinically relevant organisms stratified according to age, gender, clinical specimens and facilities. Methods Microbiological data were collected from 55 centers across 24 states in Mexico between January 1 and March 31, 2025. Bacterial identification and antimicrobial susceptibility testing were performed at each participating center using locally available methods. Data was processed using WHONET 2025. Isolates obtained from lower respiratory specimens, urine, blood, biopsies and abscesses were analyzed. Carbapenem non-susceptible isolates were further analyzed by PCR for common carbapenemase-encoding genes. Resistance frequencies were compared using the chi-square test. Results A total of 11,290 clinical isolates were analyzed, mostly from urine ( n = 7,149; 63.3%), followed by blood ( n = 1,370; 12.1%). The most prevalent was Escherichia coli ( n = 6,185; 54.8%), followed by Klebsiella pneumoniae ( n = 1,365; 12.1%) and Pseudomonas aeruginosa ( n = 1,110; 9.8%). Resistance to carbapenems in E. coli was higher in respiratory isolates (imipenem: 5.8%, p = 0.016; meropenem: 5.3%, p < 0.001), with 75.9% producing extended-spectrum ß-lactamases (ESBLs). K. pneumoniae had the highest resistance to ampicillin/sulbactam (52.5%, p = 0.028) and sulfamethoxazole/trimethoprim (62.1%, p = 0.014) in blood isolates, and 63.2% were ESBL-producers ( p = 0.001). In P. aeruginosa , urine isolates showed significantly higher resistance to ceftolozane-tazobactam (24.7%, p = 0.008), ceftazidime-avibactam (36.6%, p < 0.001), and meropenem (34.5%, p = 0.009) compared to other clinical specimens included. For A. baumannii , respiratory isolates had 73.6% resistance to meropenem ( p < 0.001). S. aureus from blood showed 25.7% resistance to oxacillin ( p < 0.004). The most frequent carbapenemase genes were bla OXA−48−like in E. coli (26/56, 46.4%), bla NDM for K. pneumoniae (7/17, 41.2%), bla OXA−24 in A. baumannii (79/108, 73.1%) and bla IMP for P. aeruginosa (18/108, 16.7%). Conclusion This surveillance study underscores the elevated levels of antimicrobial resistance, ESBL production, and carbapenemase activity among priority pathogens, including some Enterobacterales , P. aeruginosa , and A. baumannii . These findings emphasize the urgent need to strengthen epidemiologic surveillance programs in Mexican healthcare settings.

Modulation of the photodynamic activity of a cinnamoyl-coumarin–RGD peptide conjugate via cucurbit[8]uril supramolecular assembly - Benjamín Zúñiga; Paula S. Rivero-Jerez; Sofia Pérez-Del Pino; Francisco Bravo-Cabezas; Francisco Mura; Pablo Barrias; Claudio Acuña-Castillo; Mario A. Faúndez; Alexis Aspeé; Daniel Zúñiga-Núñez; Denis Fuentealba (Journal of Photochemistry and Photobiology B: Biology, 2026)

‘Building the (Im)perfect Beast’: Strategies for Identifying Appropriate Spatial Stock Assessment Model Complexity From an International, Blinded High‐Resolution Simulation Experiment - Aaron M. Berger; Daniel R. Goethel; Simon D. Hoyle; Patrick Lynch; Caren Barceló; Alistar Dunn; Brian J. Langseth; Carolina Minte‐Vera; Jemery Day; Haikun Xu; Francisco Izquierdo; Dan Fu; et al. (Fish and Fisheries, 2026)
Despite their potential to inform sustainable regional harvest and climate‐resilient fisheries management, spatial stock assessment models remain underused for management advice. To identify barriers that inhibit broader use of these methods, we conducted a blinded international simulation experiment mimicking real‐world stock assessment development when confronting spatial complexity. Seven analyst teams built spatially aggregated and spatially explicit assessment models using data simulated from high‐resolution operating models based on Indian Ocean yellowfin tuna and Ross Sea Antarctic toothfish dynamics. Each team documented how assessment software platform, data analyses, model building approach, and diagnostics influenced model complexity and realism. A consensus emerged on key assessment building approaches: (1) conduct high‐resolution data analyses to identify appropriate spatial structure; (2) start with simplified models and incrementally add complexity; (3) iteratively evaluate diagnostics to determine necessary spatial complexity; and (4) maintain models with different spatial structures to aid interpretation. The experiment also revealed several valuable insights for parameterising assessments, including consideration of data pre‐processing with spatiotemporal models to better inform data‐sparse regions; regression trees to identify fleet and spatial structure; trade‐offs in complexity between productivity and movement dynamics to achieve tractable and stable model structures; and ensemble modelling approaches to address structural uncertainty. Our findings demonstrate that international collaborations and simulation experiments are crucial for addressing challenges in implementing spatial stock assessments and for evaluating whether their added complexity is justified given management objectives. Broader collaborations are encouraged to foster innovation in fisheries management and to help recognise the practical trade‐offs between model parsimony and complexity.

Tectonomagmatic evolution of the volcano vent cluster of the Tzirate Range in Mexico - Mario E. Boijseauneau-López; Giovanni Sosa-Ceballos; Daniel Tapia-Flores; Antonio Pola; José Luis Macías; Miguel E. Castillo-Rodríguez; Xavier Bolós (Bulletin of Volcanology, 2026)
The Tzirate Range (TR; 1.5–0.93 Ma) is a volcanic vent cluster within the Michoacán-Guanajuato Volcanic Field (2.5 Ma–present), composed of effusive andesitic to rhyolitic rocks that reflect complex, multi-stage magmatic evolution. By integrating geochemical, mineralogical, isotopic, and morpho-structural data, this study reveals that magma differentiation in the TR was driven by fractional crystallization, magma mixing, and assimilation of crustal material within shallow reservoirs, under tectonic control exerted by the reactivation of basement faults. The rocks exhibit a calc-alkaline affinity with elevated δ 1 ⁸O values (+ 7.23 to + 9.43) and isotopic signatures (⁸⁷Sr/⁸⁶Sr = 0.70370–0.70431; εNd = 1.82–4.27 ± 0.33, 1σ), consistent with crustal contamination. Disequilibrium textures (e.g., resorption rims, patchy zoning) and mineral compositions (An 39–60 , En 43–79 ) reflect open-system processes and dynamic magma evolution. Hydrothermal assimilation experiments support incorporation of granitic material at ~ 880–900 °C and ~ 180 MPa. In addition, morphometric analysis of drainage networks using knickpoint detection and normalized steepness index ( K sn ) enables the identification of reactivated basement faults that control the magmatic plumbing system. Therefore, it demonstrates the utility of K sn -based morphometric analysis as a robust and complementary tool for identifying hidden tectonic systems in volcanic terrains with limited surface exposure. These findings suggest that the TR vent cluster represents a transitional stage between monogenetic and polygenetic volcanism, highlighting the influence of tectonic controls on vent distribution and long-term volcanic evolution. This interdisciplinary approach provides new insights into the mechanisms controlling the development and dynamics of volcanic clusters by characterizing their plumbing systems and structural frameworks.

Rearing performance of Scyphophorus acupunctatus Gyllenhaal (Coleoptera: Curculionidae: Dryophthorinae) on a meridic, Agave cupreata–based diet: developmental duration, survival, and reproductive parameters - Carlos Daniel Gómez-Ibarra; Selene Ramos-Ortiz; Ana Mabel Martínez-Castillo; Samuel Pineda-Guillermo; Luis Jesús Palma-Castillo; Juan Manuel Chavarrrieta-Yáñez; Yordanys Ramos; Alfonso Luna-Cruz; José Isaac Figueroa-De la Rosa (International Journal of Tropical Insect Science, 2026)

Proteomic analysis of partially purified mitochondrial fraction of beef: impact of ultimate pH and aging time on color stability - Monique Marcondes Krauskopf; Daniel Silva Antonelo; Chimenes Leal de Araújo; Júlio César de Carvalho Balieiro; Eduardo Francisquine Delgado; Ranjith Ramanathan; Carmen Josefina Contreras Castillo (Food Chemistry, 2026)

Impact of Submarine Groundwater Discharge on Microbial Communities in a Highly Anthropized Coastal Lagoon (Mar Menor, SE Spain) - Daniel Romano‐Gude; Júlia Dordal‐Soriano; Júlia Rodriguez‐Puig; Andrea G. Bravo; Irene Alorda‐Montiel; Aaron Alorda‐Kleinglass; Marc Diego‐Feliu; Cristina Romera‐Castillo; Rebeca Mallenco‐Fornies; Javier Gilabert; Jordi Garcia‐Orellana; Valentí Rodellas; et al. (Molecular Ecology, 2025)
Submarine groundwater discharge (SGD) supplies large quantities of nutrients and other terrestrial elements to coastal ecosystems, impacting marine biota and ecosystem functioning. Despite the relevance of prokaryotes for marine biogeochemistry, little is known about their responses to groundwater inputs. Here we explored the impact of SGD on the spatiotemporal patterns of prokaryotic communities from the Mar Menor (Murcia, Spain), a highly anthropized hypersaline coastal lagoon that receives large amounts of nutrient‐polluted SGD. Using 16S rRNA amplicon sequencing, activity assays, and flow cytometry, we investigated the dynamics of prokaryotic communities across the lagoon and its connected environments (freshwater streams, groundwater, soils, the sea) on two occasions. We found that the lagoon areas most influenced by SGD (i.e., sites closest to the shore) presented on average three‐fold higher heterotrophic prokaryotic protein production than the inner lagoon samples, and 2.7‐fold higher taxonomic richness. This spatial pattern was likely influenced by solutes supplied by SGD, as higher concentrations of dissolved nitrogen, silicate and SGD tracers (radium [Ra] isotopes) were found in nearshore waters. Increases in these elements also influenced the relative abundance of dominant bacterial groups (e.g., Flavobacteriales, Rhodobacterales). In autumn, increases in lagoon 224 Ra were strongly linked to higher taxonomic richness in microbial assemblages and the influx of allochthonous taxa from the catchment, pointing to seasonally variable transport of coastal groundwater microorganisms via SGD. Our study highlights SGD as an overlooked driver of prokaryotic dynamics in coastal ecosystems, and suggests that changes in this process may significantly impact microbial community structure and functioning.

Thrips (Insecta: Thysanoptera) species associated with avocado orchards in central Veracruz, Mexico - David Alarcón-Utrera; Daniel López-Lima; Carlos R. Cerdán-Cabrera; Gerardo Alvarado-Castillo; Alejandro Salinas-Castro; Gloria Carrión (International Journal of Tropical Insect Science, 2025)

Effect of air temperature, milk production and shearing on drinking water intake of Angora goats in pen during summer - Martin Calianno; Daniel A. Castillo; Santiago I. Hurtado; Saúl Deluchi; Brenda Garcia; Laura Villar; E. Sebastian Villagra; Marcos H. Easdale (Small Ruminant Research, 2025)

Spatial Structure and Decadal Spatiotemporal Distribution of the Anchoveta ( Engraulis ringens ) in the Marine Ecosystem of the Peruvian Current Between 1985 and 2024 - Pedro Ramiro Castillo; Han Xu; Gustavo Cuadros; Daniel Grados; Carlos Valdez; Rodolfo Cornejo; Marissela Pozada‐Herrera (Fisheries Oceanography, 2025)
This paper presents the spatial structure with geostatistical analysis and decadal spatiotemporal distribution of anchoveta according to the Pacific Decadal Oscillation index, its implications for the anomalous events of the oceanographic conditions of the Northern Region of the Humboldt Current System (NRHCS), and areas of high anchoveta abundance found in the analyzed period. The acoustic data came from the Hydroacoustic Pelagic Resources Assessment Surveys carried on by the Instituto del Mar del Peru (IMARPE), and the oceanographic data came from satellite images of sea surface thermal anomalies (SSTA) between 1985 and 2024. The results showed that anchoveta has had a positive linear trend, with a high positive spatial autocorrelation and a structure spatially dependent on invironmental conditions in space and time. In the cold decadal periods, anchoveta were found a little far from the coast, distributed in high concentrations mainly in the north‐central region, while in the warm decadal periods, they were found close to the coast and with greater abundance towards the central zone; exceptional was in the warm period of 1985–1988, where anchoveta distribution was wide and generally dispersed. The trend in the warm decadal periods was negative, and in the decadal periods, it was positively influenced by El Niño events: 1997–1998 and 2015–2016, with a decrease in biomass recorded in 1998 and 2015. In the last cold period, 2017–2024, it was influenced by the warm year of 2023. Between 2000 and 2024, anchoveta biomass averaged 8.26 million tons, with an average biomass of 7.46 million tons for the north‐central region between 2004 and 2024.

Distribution and abundance of squat lobster (Pleuroncodes monodon) and its association with anchoveta in the coastal zone of the Peruvian Current (1998–2024) - Pedro Ramiro Castillo; Luis La Cruz; Carlos Valdez; Gustavo Cuadros; Ketty Ferrel; Marissela Pozada-Herrera; Rodolfo Cornejo; Aníbal Aliaga; Daniel Grados (Frontiers in Marine Science, 2025)
The squat lobster or munida ( Pleuroncodes monodon ) is one of the most abundant species in the coastal zone of the Peruvian Current. Due to its high incidence of occurrence and biomass, it has been monitored since 1998 by the Instituto del Mar del Perú (IMARPE) through the Hydroacoustic Assessment Surveys for Anchoveta and Other Pelagic Resources. In this study, 59 surveys conducted between 1998 and 2024 were analyzed to study the spatial distribution, abundance, and ecological relationship of munida with anchoveta ( Engraulis ringens ). The results showed that between 1998 and 2000, munida expanded its distribution northward along the Peruvian coast, while from 2001 onward its range remained relatively stable. A clear seasonal pattern was identified: during winter and spring, both the distribution area and inertia increased, and the species tended to occur farther from the coast, whereas in summer and autumn the distribution contracted, except during anomalous oceanographic events (e.g., warm or cold conditions). Vertically, munida generally inhabited the surface layer down to approximately 168 m, although during the 2015 -2016 El Niño event it was recorded as deep as 203 m. The average biomass throughout the study period was close to 2.04 million tons, with a maximum of 5.38 million tons recorded during survey 1703-04. Munida was also the species most closely associated with anchoveta, and when both occurred together, their interaction varied depending on the time of day, probably reflecting diel vertical migration and differential aggregation behaviors. These findings suggest that munida is a key component of the Peruvian Current ecosystem, whose variability is influenced both by seasonal cycles and by anomalous oceanographic conditions, and that its association with anchoveta may have implications for ecosystem functioning and fisheries management in the region.

The Health Benefits of Probiotic Lactiplantibacillus plantarum: A Systematic Review and Meta-Analysis - Amal Aljohani; Noha Rashwan; Shruti Vasani; Ahmed Alkhawashki; Tong Tong Wu; Xingyi Lu; Daniel A. Castillo; Jin Xiao (Probiotics and Antimicrobial Proteins, 2025)
To ensure effective administration of probiotics in clinical practice, it is crucial to comprehend the specific strains and their association with human health. Therefore, we conducted a systematic review and meta-analysis to evaluate the scientific evidence on the impact of Lactiplantibacillus plantarum probiotic consumption on human health. Out of 11,831 records, 135 studies were assessed qualitatively, and 18 studies were included in the meta-analysis. This systematic review demonstrated that probiotic supplementation with L. plantarum , either alone or in combination, can significantly improve outcomes for patients with specific medical conditions. Meta-analysis revealed notable benefits in periodontal health, evidenced by reduced pocket depth and bleeding on probing ( p < 0.001); in gastroenterological health, marked by significant reductions in abdominal pain ( p < 0.001); and in infectious disease, through a reduction in C-reactive protein levels ( p < 0.001). Cardiovascular benefits included lowered total cholesterol and low-density lipoprotein cholesterol in the L. plantarum intervention group ( p < 0.05). Our study’s clinical significance highlights the importance of considering probiotic strain and their application to specific diseases when planning future studies and clinical interventions, emphasizing the need for further research in this area.

Body mass index and prognosis of infective endocarditis - Raquel Frías-García; Patricia Muñoz García; Marina Machado Vilchez; Gregorio Cuerpo Caballero; Raquel Rodríguez-García; M Ángeles Rodríguez-Esteban; M Carmen Fariñas-Álvarez; José M. Miró Meda; Andrea Gutiérrez Villanueva; Guillermo Ojeda-Burgos; Ane Josune Goikoetxea-Agirre; Marina Bernal Palacios; et al. (Infectious Diseases, 2025)

Mitochondrial proteome basis for the biological variations in beef color stability of longissimus lumborum muscle differing in ultimate pH and packaging methods - Monique Marcondes Krauskopf; Daniel S. Antonelo; Chimenes Darlan Leal de Araújo; Júlio César de Carvalho Balieiro; Eduardo Francisquine Delgado; Ranjith Ramanathan; Carmen Josefina Contreras Castillo (Meat Science, 2025)

A single-tree approach to determine climate-growth patterns of European beech and their seasonality in the species southern distribution area - Roberto Serrano-Notivoli; Jernej Jevšenak; Edurne Martinez del Castillo; Katarina Čufar; Nina Škrk-Dolar; Giovanna Battipaglia; Jesus Julio Camarero; Andrew Hacket Pain; Alistair Jump; Renzo Motta; Paola Nola; Momchil Panayotov; et al. (Agricultural and Forest Meteorology, 2025)

Pathogenic impact of Vibrio spp. in scallop hemolymph: Implications for health in aquaculture - Roxana González; Mauricio Peña-Jaña; Rodrigo Rojas; Daniel Oyanedel; Carlos Henríquez-Castillo; Orlando Astudillo; Paulina Schmitt; Katherina Brokordt (Aquaculture, 2025)

Age and Length at Maturity of Pelagic Thresher (Alopias pelagicus) in the Mexican Pacific - L. Daniel Carrillo-Colín; J. Fernando Márquez-Farías; J. Leonardo Castillo-Géniz; Oscar G. Zamora-García (Thalassas: An International Journal of Marine Sciences, 2025)

Occurrence of pharmaceuticals in muscle tissue of red drum (Sciaenops ocellatus) across subtropical estuaries: Comparison to blood plasma and implications for human exposure - W. Ryan James; Nicholas A. Castillo; Andy Distrubell; Shakira Trabelsi; Rolando O. Santos; Daniel Cerveny; Ryan J. Rezek; Ross E. Boucek; Aaron J. Adams; Jerker Fick; Tomas Brodin; Jennifer S. Rehage (Science of The Total Environment, 2025)

Using satellite imagery to track the development of the green belt of Astana, Kazakhstan: A remote sensing perspective on artificial forestry development - Erin Driscoll; Jorge Portugues Fernandez del Castillo; Dana Bazarkulova; Daniel Hicks; Kirsten de Beurs (Remote Sensing Applications: Society and Environment, 2025)

Advancing the enzymatic removal of antibiotics with unspecific peroxygenase and vanadium chloroperoxidase - Sabrina de Boer; Daniel Sastre; Aly Castillo; Sabela Balboa Méndez; Frank Hollmann; Marta Lores; Andreas Schäffer; María Teresa Moreira (Journal of Environmental Chemical Engineering, 2025)

Are all renewable energy sources the same? A comparative analysis of public perceptions and preferences for renewable energy types in Southeast Asian cities - Daniel del Barrio Alvarez; Nan Wang; Masahiro Sugiyama; Masako Numata; Truong Dang Thuy; Azlina Abd Aziz; Rosalina Palanca-Tan; Aung Ze Ya; Ariel Anshory Yusuf; Awang Noor Abd. Ghani; Gem Castillo; Martin Daniel Siyaranamual; et al. (Sustainability Science, 2025)
The realization of a sustainable energy transition in Southeast Asia will require the overcoming of the current high reliance on fossil fuels in the energy mix and the steady and rapid growth in energy demand in the region. To achieve an economically, socially, and environmentally sustainable energy transition in the region, it is vital to utilize all available renewable energy sources to the greatest extent possible. It is therefore essential to gain an understanding of how citizens in each country perceive the available renewables. However, the majority of existing literature in this region has been constrained by a narrow focus on a comparison between fossil and renewable energy. Furthermore, while previous research has predominantly concentrated on single-country analyses, there are significant implications that could be disseminated across ASEAN countries. In light of the aforementioned limitations of existing literature, this paper aims to make a contribution by undertaking a comparative analysis of public preferences for renewable energy sources in eight major urban areas in seven Southeast Asian countries. The findings of this study indicate that, while climate change (or global warming) is perceived as a significant issue, it is often regarded as a secondary concern compared to other environmental issues. This is despite the fact that many of these issues are closely interlinked with and would be exacerbated by climate change. Furthermore, the findings suggest that solar energy is the most preferred renewable source across all urban areas surveyed. In contrast, bioenergy (or biomass) is generally the least preferred source of energy in all cities. There is considerable variation in perceptions of wind, hydro, and geothermal energy, with a high degree of variability between and within countries. These similarities and differences in preferences for renewable energy sources appear to be associated with varying levels of knowledge or familiarity with each source, which is consistent with differing willingness to pay for each source. These findings highlight the necessity for policies that address this apparent lack of understanding of how the transition to a sustainable energy system and each renewable energy technology can help mitigate the impact of environmental problems highlighted in each society.

Metro Manila households’ willingness to pay for renewable energy as a climate change mitigation measure: a CVM study - Rosalina Palanca-Tan; Masahiro Sugiyama; Daniel del Barrio Alvarez; Gem B. Castillo; Nelson Matthew P. Tan (Sustainability Science, 2025)

Salt-regulated prepartum supplementation and parity effects on maternal performance, wool growth, and lamb development in Merino ewes grazing in semi-arid steppes - Marcela Cueto; Jimena Fernandez; María Macarena Bruno-Galarraga; Alejandro Gibbons; Maximiliano Riquelme; Daniel Castillo; Micaela Tesan; Barbara Schaap; María Laura Villar; Sebastián Villagra (Animal Feed Science and Technology, 2025)

Wounding after cocultivation improves somatic embryogenesis response and agrobacterium-mediated genetic transformation of Coffea canephora L. - Daniel Pérez-Pascual; Doribet Jiménez-Guillen; Lourdes María Santamaría-Poot; Jorge Cime-Castillo; José Juan Zúñiga-Aguilar (South African Journal of Botany, 2025)

12,000 years away from the sea: Long-term circulation of Pacific shells in the Semiarid North of Chile (South America) - Daniel Hernández Castillo; Andrés Troncoso; César Méndez; Daniel Pascual; Felipe Armstrong; Amalia Nuevo-Delaunay; Sebastián Grasset; Isidora Pérez; Francisca Vera; Manuela Delgado; Antonia Escudero; Mariela Pino; et al. (Quaternary Science Reviews, 2025)

Influence of lipid and metabolite profiles of mitochondrial fraction on pH and color stability of longissimus lumborum muscle with different ultimate beef pH - Monique Marcondes Krauskopf; Daniel Silva Antonelo; Chimenes Darlan Leal de Araújo; Beatriz Garcia Lopes; Gabriel Henrique Ribeiro; Luiz Alberto Colnago; Júlio César de Carvalho Balieiro; Eduardo Francisquine Delgado; Rajith Ramanathan; Carmen Josefina Contreras Castillo (Meat Science, 2025)

Lipidome and metabolome profiling of longissimus lumborum beef with different ultimate pH and postmortem aging - Alan Giovanini de Oliveira Sartori; Daniel Silva Antonelo; Gabriel Henrique Ribeiro; Luiz Alberto Colnago; Júlio César de Carvalho Balieiro; Eduardo Francisquine Delgado; Carmen Josefina Contreras Castillo (Meat Science, 2024)

In-depth exploration of the high and normal pH beef proteome: First insights emphasizing the dynamic protein changes in Longissimus thoracis muscle from pasture-finished Nellore bulls over different postmortem times - Iliani Patinho; Daniel S. Antonelo; Eduardo F. Delgado; Laura Alessandroni; Júlio C.C. Balieiro; Carmen J. Contreras Castillo; Mohammed Gagaoua (Meat Science, 2024)

Comparative analysis of commercial cleaning and disinfection formulations and protocols for effective eradication of biofilms formed by a Pseudomonas fluorescens strain isolated from a poultry meat plant - Natalia Merino; Carlota García-Castillo; Daniel Berdejo; Elisa Pagán; Diego García-Gonzalo; Rafael Pagán (Food Control, 2024)

Defining an ageing-related pathology, disease or syndrome: International Consensus Statement - Emma Short; Ian M. Adcock; Bilal Al-Sarireh; Ann Ager; Ramzi Ajjan; Naveed Akbar; Michael A. Akeroyd; Ghada Alsaleh; Ghada Al-Sharbatee; Kambiz Alavian; Winfried Amoaku; Julie Andersen; et al. (GeroScience, 2024)
Around the world, individuals are living longer, but an increased average lifespan does not always equate to an increased health span. With advancing age, the increased prevalence of ageing-related diseases can have a significant impact on health status, functional capacity and quality of life. It is therefore vital to develop comprehensive classification and staging systems for ageing-related pathologies, diseases and syndromes. This will allow societies to better identify, quantify, understand and meet the healthcare, workforce, well-being and socioeconomic needs of ageing populations, whilst supporting the development and utilisation of interventions to prevent or to slow, halt or reverse the progression of ageing-related pathologies. The foundation for developing such classification and staging systems is to define the scope of what constitutes an ageing-related pathology, disease or syndrome. To this end, a consensus meeting was hosted by the International Consortium to Classify Ageing-Related Pathologies (ICCARP), on February 19, 2024, in Cardiff, UK, and was attended by 150 recognised experts. Discussions and voting were centred on provisional criteria that had been distributed prior to the meeting. The participants debated and voted on these. Each criterion required a consensus agreement of ≥ 70% for approval. The accepted criteria for an ageing-related pathology, disease or syndrome were (1) develops and/or progresses with increasing chronological age; (2) should be associated with, or contribute to, functional decline or an increased susceptibility to functional decline and (3) evidenced by studies in humans. Criteria for an ageing-related pathology, disease or syndrome have been agreed by an international consortium of subject experts. These criteria will now be used by the ICCARP for the classification and ultimately staging of ageing-related pathologies, diseases and syndromes.

Wind dispersed tree species have greater maximum height - Ferry Slik; Bruno X. Pinho; Daniel M. Griffith; Edward Webb; Akhilesh Singh Raghubanshi; Adriano C. Quaresma; Aida Cuni Sanchez; Aisha Sultana; Alexandre F. Souza; Andreas Ensslin; Andreas Hemp; Andrew Lowe; et al. (Global Ecology and Biogeography, 2024)
Aim We test the hypothesis that wind dispersal is more common among emergent tree species given that being tall increases the likelihood of effective seed dispersal. Location Americas, Africa and the Asia‐Pacific. Time period 1970–2020. Major taxa studied Gymnosperms and Angiosperms. Methods We used a dataset consisting of tree inventories from 2821 plots across three biogeographic regions (Americas, Africa and Asia‐Pacific), including dry and wet forests, to determine the maximum height and dispersal strategy of 5314 tree species. A web search was used to determine whether species were wind‐dispersed. We compared differences in tree species maximum height between biogeographic regions and examined the relationship between species maximum height and wind dispersal using logistic regression. We also tested whether emergent tree species, that is species with at least one individual taller than the 95% height percentile in one or more plots, were disproportionally wind‐dispersed in dry and wet forests within each biogeographic region. Results Our dataset provides maximum height values for 5314 tree species, of which more than half (2914) had no record of this trait in existing global databases. We found that, on average, tree species in the Americas have lower maximum heights compared to those in Africa and the Asia Pacific. The probability of wind dispersal increased significantly with tree species maximum height and was significantly higher among emergent than non‐emergent tree species in both dry and wet forests in all three biogeographic regions. Main conclusion Wind dispersal is more prevalent in tall, emergent tree species than in non‐emergent species and may thus be an important factor in the evolution of tree species maximum height. By providing the most comprehensive dataset so far of tree species maximum height and wind dispersal strategies, this study paves the way for advancing our understanding of the eco‐evolutionary drivers of tree size.

Impact of replacing protein pellets with soybean grain on nutrient utilization and the rumen and blood parameters of feedlot cattle under tropical conditions - Daniel Henrique Souza Tavares; Julián Andrés Castillo Vargas; Vera Lúcia de Araújo Bozorg; Jose Neuman Miranda Neiva; José Helder de Andrade Moura; Ithalo Barros Freitas; Thays Matias da Silva Pinto; Luciano Fernandes Sousa; Fabrícia Rocha Chaves Miotto (Tropical Animal Health and Production, 2024)

A multidisciplinary approach to analyze the antimicrobial resistance in natural ecosystems - Kinndle Blanco-Peña; Francisco Quesada-Alvarado; Denis Salas-González; Sandra Estrada-König; Roberto Salom-Pérez; Stephanny Arroyo-Arce; Adriana Villalobos-Araya; Josué Rivera-Castillo; Bárbara Martín-Maldonado; Daniel Corrales-Gutiérrez; Valeria Gallardo-Castro; Gustavo Gutiérrez-Espeleta; et al. (Environmental Research, 2024)

Prophages carrying Zot toxins on different Vibrio genomes: A comprehensive assessment using multilayer networks - Esteban F. Soto; Melissa Alegría; Felipe Sepúlveda; Katherine García; Gastón Higuera; Daniel Castillo; Francisco E. Fontúrbel; Roberto Bastías (Environmental Microbiology, 2024)
Vibrios, a group of bacteria that are among the most abundant in marine environments, include several species such as Vibrio cholerae and Vibrio parahaemolyticus , which can be pathogenic to humans. Some species of Vibrio contain prophages within their genomes. These prophages can carry genes that code for toxins, such as the zonula occludens toxin (Zot), which contribute to bacterial virulence. Understanding the association between different Vibrio species, prophages and Zot genes can provide insights into their ecological interactions. In this study, we evaluated 4619 Vibrio genomes from 127 species to detect the presence of prophages carrying the Zot toxin. We found 2030 potential prophages with zot ‐like genes in 43 Vibrio species, showing a non‐random association within a primarily modular interaction network. Some prophages, such as CTX or Vf33, were associated with specific species. In contrast, prophages phiVCY and VfO3K6 were found in 28 and 20 Vibrio species, respectively. We also identified six clusters of Zot‐like sequences in prophages, with the ZOT2 cluster being the most frequent, present in 34 Vibrio species. This analysis helps to understand the distribution patterns of zot ‐containing prophages across Vibrio genomes and the potential routes of Zot‐like toxin dissemination.

A global analysis of field body temperatures of active squamates in relation to climate and behaviour - Shahar Dubiner; Rocío Aguilar; Rodolfo O. Anderson; Diego M. Arenas Moreno; Luciano J. Avila; Estefania Boada‐Viteri; Martin Castillo; David G. Chapple; Christian O. Chukwuka; Alison Cree; Félix B. Cruz; Guarino R. Colli; et al. (Global Ecology and Biogeography, 2024)
Aim Squamate fitness is affected by body temperature, which in turn is influenced by environmental temperatures and, in many species, by exposure to solar radiation. The biophysical drivers of body temperature have been widely studied, but we lack an integrative synthesis of actual body temperatures experienced in the field, and their relationships to environmental temperatures, across phylogeny, behaviour and climate. Location Global (25 countries on six continents). Taxa Squamates (210 species, representing 25 families). Methods We measured the body temperatures of 20,231 individuals of squamates in the field while they were active. We examined how body temperatures vary with substrate and air temperatures across taxa, climates and behaviours (basking and diel activity). Results Heliothermic lizards had the highest body temperatures. Their body temperatures were the most weakly correlated with substrate and air temperatures. Body temperatures of non‐heliothermic diurnal lizards were similar to heliotherms in relation to air temperature, but similar to nocturnal species in relation to substrate temperatures. The correlation of body temperature with air and substrate temperatures was stronger in diurnal snakes and non‐heliothermic lizards than in heliotherms. Body‐substrate and body‐air temperature correlations varied with mean annual temperatures in all diurnal squamates, especially in heliotherms. Thermal relations vary with behaviour (heliothermy, nocturnality) in cold climates but converge towards the same relation in warm climates. Non‐heliotherms and nocturnal species body temperatures are better explained by substrate temperature than by air temperature. Body temperature distributions become left‐skewed in warmer‐bodied species, especially in colder climates. Main Conclusions Squamate body temperatures, their frequency distributions and their relation to environmental temperature, are globally influenced by behavioural and climatic factors. For all temperatures and climates, heliothermic species' body temperatures are consistently higher and more stable than in other species, but in regions with warmer climate these differences become less pronounced. A comparable variation was found in non‐heliotherms, but in not nocturnal species whose body temperatures were similar to air and substrate irrespective of the macroclimatic context.

Antibiotic resistance in wildlife from Antarctic Peninsula - Josefina Gutiérrez; Daniel González-Acuña; Danny Fuentes-Castillo; Karina Fierro; Carlos Hernández; Loreto Zapata; Claudio Verdugo (Science of The Total Environment, 2024)

Straw digestibility in rice: Novel insights from pyrolysis GC-MS and biomass phenotyping - Mariana P. Silva; Caragh Whitehead; Reynante L. Ordonio; Trinidad C. Fernando; Mark Philip B. Castillo; Jeremias L. Ordonio; Tony Larson; Daniel J. Upton; Susan E. Hartley; Leonardo D. Gomez (Biomass and Bioenergy, 2024)

Associations between urban greenspace and depressive symptoms in Mexico's cities using different greenspace metrics - Maryia Bakhtsiyarava; Yang Ju; Mika Moran; Daniel A. Rodríguez; Iryna Dronova; Xavier Delclòs-Alió; Kari Moore; Marianela Castillo-Riquelme; Cecilia Anza-Ramirez (Applied Geography, 2024)

Incorporating high-resolution climate, remote sensing and topographic data to map annual forest growth in central and eastern Europe - Jernej Jevšenak; Marcin Klisz; Jiří Mašek; Vojtěch Čada; Pavel Janda; Miroslav Svoboda; Ondřej Vostarek; Vaclav Treml; Ernst van der Maaten; Andrei Popa; Ionel Popa; Marieke van der Maaten-Theunissen; et al. (Science of The Total Environment, 2024)

The critical period for yield and grain protein determination in quinoa (Chenopodium quinoa Willd.) - Santiago C. Vásquez; Alejandro del Pozo; Dalma Castillo; Iván Matus; Luz Gómez-Pando; Diego Zamudio-Ayala; Cesar M. Mignone; H. Daniel Bertero; Daniel F. Calderini (Field Crops Research, 2024)

Human health risk assessment due to mercury use in gold mining areas in the Ecuadorian Andean region - Carlos Mestanza-Ramón; Samantha Jiménez-Oyola; Alex Vinicio Gavilanes Montoya; Danny Daniel Castillo Vizuete; Giovanni D'Orio; Juan Cedeño-Laje; Doménica Urdánigo; Salvatore Straface (Chemosphere, 2023)

Exposure to secondhand and thirdhand smoke in private vehicles: Measurements in air and dust samples - Xavier Continente; Elisabet Henderson; Laura López-González; Esteve Fernández; Olena Tigova; Sean Semple; Rachel O'Donnell; Ana Navas-Acién; Núria Cortés-Francisco; Noelia Ramírez; Ruaraidh Dobson; Maria José López; et al. (Environmental Research, 2023)

Assessment of Hg pollution in stream waters and human health risk in areas impacted by mining activities in the Ecuadorian Amazon - Carlos Mestanza-Ramón; Samantha Jiménez-Oyola; Alex Vinicio Gavilanes Montoya; Danny Daniel Castillo Vizuete; Giovanni D’Orio; Juan Cedeño-Laje; Salvatore Straface (Environmental Geochemistry and Health, 2023)
Illegal gold mining activities have contributed to the release and mobilization of Hg and environmental degradation in many parts of the world. This study aims to determine the concentration of Hg in five provinces of the Amazon Region of Ecuador, in addition to assessing the risk to human health of exposed populations, applying deterministic and probabilistic methods. For this purpose, 147 water samples were collected in rivers and streams crossing and/or located near mining areas. As a result, 100% of the samples analyzed exceeded the maximum permissible limit (MPL) according to the water quality criteria for the preservation of aquatic life of the Ecuadorian regulations, while 7% of the samples exceeded the MPL for drinking water. On the other hand, considering the European Environmental Quality Standard (EQS) for surface water bodies, in our study, 100% of the samples exceed the maximum permissible limit (0.07 µg/L), and with respect to the Canadian water quality guidelines, 35% of the samples exceed the permissible limit (0.001 mg/l) for drinking water, and 100% of the samples exceed the limit for life in water bodies (0.0001 mg/l). The risk assessment revealed that the probability of developing adverse health effects from exposure to Hg is below the recommended limits according to the probabilistic assessment; this is in relation to the criterion of residential and recreational use of water resources. However, it was identified that the child population doubles the acceptable systemic risk level according to the results of the deterministic assessment in the residential scenario. This information can be used by decision-makers to implement strategies to reduce Hg contamination and exposure of the population in Ecuadorian Amazonian rivers.

International Lima Bean Network: from the origin of the species to modern plant breeding - Jaime Martínez-Castillo; Ademir S. F. Araujo; María I. Chacón-Sánchez; Luis G. Santos; Angela C. A. Lopes; Kimberly Gibson; Regina L. F. Gomes; Rubén H. Andueza-Noh; Elena Bitochi; Horacio S. Ballina-Gómez; Eduardo Peralta; Ernesto Ormeño-Orrillo; et al. (Genetic Resources and Crop Evolution, 2023)

Comparative Life Cycle Assessment (LCA) on battery electric and combustion engine motorcycles in Taiwan - Falk Schneider; Daniel Sebastián Castillo Castro; Kuo-Che Weng; Cheng-Hsiang Shei; Hsin-Tien Lin (Journal of Cleaner Production, 2023)

Evaluation of the Importance of rural tourist attractions in Riobamba Canton, Ecuador - Danny Daniel Castillo Vizuete; Alex Vinicio Gavilanes Montoya; Gabriela Estefanía Román Santamaría (Environment Systems and Decisions, 2023)

Sitotroga cerealella-resistant mexican maize races (Zea mays L.), new sources of resistance for commercial maize breeding - Paola Macías-Estrada; Francisco Orozco-González; Gloria Castellanos-Pérez; Adán Castillo-Rosales; Adalberto Ortega-Ortega; Rosa A. Malvar; Daniel Padilla-Chacón; José C. Jiménez-Galindo (Cereal Research Communications, 2023)
Sitotroga cerealella (Oliv.) (Lepidoptera: Gelechiidae) is one of the most important post-harvest pests of maize Zea mays L. Some Mexican maize races ( Z. mays ) could be a novel source of resistance against S. cerealella to improve commercial maize varieties, lines and hybrids. We studied the resistance of Mexican maize races, recollected at Chihuahua State to S. cerealella . We focused on antibiosis and tolerance of maize to S. cerealella . Cristalino-079 maize race shows low level of consumption in grams and percentage, increased larvae mortality before to entering the seed. In addition, Cristalino-079 reduced first adult’s generation and show the largest biological cycle. Due to the small number of emerged adults, there was very little grain weight loss in resistant maize race. The compound that causes high mortality of larvae before to entering the grain is in the pericarp of resistant maize races. The compound that causes longest development time is in the endosperm and embryo. Cristalino-079 show the better level of resistance to S. cerealella infestation in almost all traits studied and this can be used as source of resistance for maize breeding.

Composites of Co-Al hydrotalcites and carbon nanomaterials for photocatalytic H2 production - Dolores G. Gil-Gavilán; Daniel Cosano; Miguel Castillo-Rodríguez; Gustavo de Miguel; Dolores Esquivel; César Jiménez-Sanchidrián; José R. Ruiz; Francisco J. Romero-Salguero (Applied Clay Science, 2023)

Children's interaction with ecosystem services in a mangrove forest: Perceptions of fisherfolks on the involvement of minors in fishing activities in the Gulf of Fonseca in Honduras - Isidro Maya Jariego; Daniel Holgado; Andrea Cecilia Castillo; David Florido del Corral; Sílvia Gòmez Mestres (Ocean & Coastal Management, 2023)

Cross-sectional associations of persistent organic pollutants measured in adipose tissue and metabolic syndrome in clinically diagnosed middle-aged adults - Iris Reina-Pérez; Francisco Artacho-Cordón; Vicente Mustieles; Daniel Castellano-Castillo; Fernando Cardona; Inmaculada Jiménez-Díaz; Jose A. López-Medina; Juan Alcaide; Luis Ocaña-Wilhelmi; Luz M. Iribarne-Durán; Juan P. Arrebola; Nicolás Olea; et al. (Environmental Research, 2023)

Aerosolized aqueous dust extracts collected near a drying lake trigger acute neutrophilic pulmonary inflammation reminiscent of microbial innate immune ligands - Trevor A. Biddle; Keziyah Yisrael; Ryan Drover; Qi Li; Mia R. Maltz; Talyssa M. Topacio; Jasmine Yu; Diana Del Castillo; Daniel Gonzales; Hannah L. Freund; Mark P. Swenson; Malia L. Shapiro; et al. (Science of The Total Environment, 2023)

Measurement of airborne nicotine, as a marker of secondhand smoke exposure, in homes with residents who smoke in 9 European countries - Elisabet Henderson; Luis A. Rodriguez Guerrero; Xavier Continente; Esteve Fernández; Olena Tigova; Nuria Cortés-Francisco; Sean Semple; Ruaraidh Dobson; Anna Tzortzi; Vergina K. Vyzikidou; Giuseppe Gorini; Gergana Geshanova; et al. (Environmental Research, 2023)

Reversible mutations in gliding motility and virulence genes: A flexible and efficient phage defence mechanism in Flavobacterium psychrophilum - Jóhanna Jørgensen; Krister Sundell; Daniel Castillo; Liv S. Dramshøj; Natasja B. Jørgensen; Susie B. Madsen; Lotta Landor; Tom Wiklund; Valentina L. Donati; Lone Madsen; Inger Dalsgaard; Mathias Middelboe (Environmental Microbiology, 2022)
Flavobacteria are among the most important pathogens in freshwater salmonid aquaculture worldwide. Due to concerns regarding development of antibiotic resistance, phage therapy has been proposed as a solution to decrease pathogen load. However, application of phages is challenged by the development of phage resistance, and knowledge of the mechanisms and implications of phage resistance is therefore required. To study this, 27 phage‐resistant isolates of F. psychrophilum were genome sequenced and characterized to identify genetic modifications and evaluate changes in phenotypic traits, including virulence against rainbow trout. Phage‐resistant isolates showed reduction or loss of gliding motility, proteolytic activity, and adhesion to surfaces, and most isolates were completely non‐virulent against rainbow trout fry. Genomic analysis revealed that most phage‐resistant isolates had mutations in genes associated with gliding motility and virulence. Reversal of these mutations in a sub‐set of isolates led to regained motility, proteolytic activity, virulence and phage susceptibility. Although costly, the fast generation of phage resistance driven by single, reversible mutations likely represents a flexible and efficient phage defence mechanism in F. psychrophilum . The results further suggest that phage administration in aquaculture systems to prevent F. psychrophilum outbreaks selects for non‐virulent phage‐resistant phenotypes.

Characteristics of anchoveta ( Engraulis ringens ) schools in the optimum zone and the physiological stress zone of its distribution between 2011 and 2021 - Pedro Ramiro Castillo; Cecilia Peña; Daniel Grados; Luis La Cruz; Carlos Valdez; Marissela Pozada‐Herrera; Rodolfo Cornejo (Fisheries Oceanography, 2022)
This study has considered anchoveta acoustic data from the Pelagic Resources Hydroacoustic Assessment Surveys carried out by the Peruvian Sea Institute (IMARPE) and free access satellite data (HYCOM and MODIS from the USA) of some oceanographic variables between the period 2011 and 2021, to know the oceanographic conditions, characteristics of schools and size structure in the optimum zone (OZ) and in the physiological stress zone (PSZ), of their total distribution. The OZ is determined by the extent of the Cold Coastal Waters (CCW), and the PSZ is determined by the mixing of waters, to the north by the CCW‐ESW (Equatorial Surface Waters) and to the west between the CCW‐SSW (Subtropical Surface Waters). The range of sea surface temperature and salinity in the PSZ (16.1–25.0°C and 34.65–35.29, respectively) was wider than in the OZ (14.5–24.0°C and 34.65–35.20, respectively), where a higher number of schools were recorded. Our analyses showed that the morphometric and energetic acoustic descriptors of anchoveta schools in the summer were higher during summers compared to springs. In terms of positional characteristics, the mean depth of the schools in the PSZ was slightly greater than in the OZ. The total size structure of anchoveta in the OZ consisted mainly of juvenile specimens (less than 12 cm total length) in the summer of 2011 and 2013–2014 and in the spring between 2014–2017 and 2021. In the PSZ, adult specimens (greater than 12 cm total length) predominated in summer between 2011–2013, 2015, 2018, and 2021 and in spring between 2011–2013, 2015, and between 2018–2021. However, specimens greater than 10 cm in total length were found in the PSZ. Knowledge of the location of this zone away from the coast will allow a high probability of anchoveta capture of adult specimens during fishing periods.

Nonalcoholic Steatohepatitis Modifies Serum Iron-Related Variables in Patients with Morbid Obesity - Anna Hernández-Aguilera; Núria Casacuberta; Helena Castañé; Montserrat Fibla; Salvador Fernández-Arroyo; Isabel Fort-Gallifa; Marta París; Fàtima Sabench; Daniel Del Castillo; Gerard Baiges-Gaya; Elisabet Rodríguez-Tomàs; Teresa Sans; et al. (Biological Trace Element Research, 2021)

Correction to: Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Resource availability and heterogeneity shape the self‐organisation of regular spatial patterning - Jessica A. Castillo Vardaro; Juan A. Bonachela; Christopher C. M. Baker; Malin L. Pinsky; Daniel F. Doak; Robert M. Pringle; Corina E. Tarnita (Ecology Letters, 2021)
Explaining large‐scale ordered patterns and their effects on ecosystem functioning is a fundamental and controversial challenge in ecology. Here, we coupled empirical and theoretical approaches to explore how competition and spatial heterogeneity govern the regularity of colony dispersion in fungus‐farming termites. Individuals from different colonies fought fiercely, and inter‐nest distances were greater when nests were large and resources scarce—as expected if competition is strong, large colonies require more resources and foraging area scales with resource availability. Building these principles into a model of inter‐colony competition showed that highly ordered patterns emerged under high resource availability and low resource heterogeneity. Analysis of this dynamical model provided novel insights into the mechanisms that modulate pattern regularity and the emergent effects of these patterns on system‐wide productivity. Our results show how environmental context shapes pattern formation by social‐insect ecosystem engineers, which offers one explanation for the marked variability observed across ecosystems.

Genome‐informed approach to identify genetic determinants of Flavobacterium psychrophilum phage susceptibility - Castillo Daniel; Jørgensen Johanna; Sundell Krister; Madsen Lone; Dalsgaard Inger; Wiklund Tom; Middelboe Mathias (Environmental Microbiology, 2021)
Summary The fish pathogen Flavobacterium psychrophilum infects farmed salmonids worldwide, and application of bacteriophages has been suggested for controlling disease outbreaks in aquaculture. Successful application of phages requires detailed knowledge about the variability in phage susceptibility of the host communities. In this study, we analysed the genetic diversity of F. psychrophilum hosts and phages from the Baltic Sea area to identify genetic determinants of phage‐host interaction patterns. A host range analysis of 103 phages tested against 177 F. psychrophilum strains (18 231 phage–host interactions) identified nine phage clusters, infecting from 10% to 91% of the strain collection. The core genome‐based comparison of 35 F. psychrophilum isolates revealed an extremely low overall genomic diversity (>99.5% similarity). However, a small subset of 16 ORFs, including genes involved in the type IX secretion system (T9SS), gliding motility and hypothetical cell‐surface related proteins, exhibited a highly elevated genetic diversity. These specific genetic variations were linked to variability in phage infection patterns obtained from experimental studies, indicating that these genes are key determinants of phage susceptibility. These findings provide novel insights on the molecular mechanisms determining phage susceptibility in F. psychrophilum and emphasizes the importance of phages as drivers of core genomic diversity in this pathogen.

Angiogenesis, hereditary hemorrhagic telangiectasia and COVID-19 - Antoni Riera-Mestre; Adriana Iriarte; Manuela Moreno; Raul del Castillo; Daniel López-Wolf (Angiogenesis, 2021)
Hereditary hemorrhagic telangiectasia (HHT) is a rare autosomal-dominant disease characterized by pathologic angiogenesis that provokes vascular overgrowth. The evidence about the influence of Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2) in patients with rare diseases is scarce. We aimed to know the prevalence of coronavirus disease 2019 (COVID-19) in HHT patients. The HHT pathogenic angiogenesis and endothelial injury in COVID-19 are discussed using data from RiHHTa (Computerized Registry of Hereditary Hemorrhagic Telangiectasia) registry. RiHHTa is an open, multicenter, prospective, observational registry including adult patients with HHT. A 27-item survey that captured clinical data of admitted HHT patients for COVID-19 was distributed to all RiHHTa investigators from June 8th to June 24th 2020. Only one out of 1177 HHT patients was admitted for COVID-19 pneumonia. She is a 74 years-old woman with a pathogenic variant in ACVRL1 gene. Her clinical course did not involve mechanical ventilation or worsening epistaxis, and she was successfully discharged after two weeks. The endothelial damage and the consequent angiogenic process in COVID-19 patients deserve further investigation.

Prior cortical activity differences during an action observation plus motor imagery task related to motor adaptation performance of a coordinated multi-limb complex task - J. Ignacio Serrano; Daniel Muñoz-García; Raúl Ferrer-Peña; Victor D’eudeville; Marta Brero; Maxime Boisson; M. Dolores del Castillo (Cognitive Neurodynamics, 2020)

Spatial patterning of soil microbial communities created by fungus‐farming termites - Christopher C. M. Baker; Jessica A. Castillo Vardaro; Daniel F. Doak; Johan Pansu; Jérémy Puissant; Robert M. Pringle; Corina E. Tarnita (Molecular Ecology, 2020)
Spatially overdispersed mounds of fungus‐farming termites (Macrotermitinae) are hotspots of nutrient availability and primary productivity in tropical savannas, creating spatial heterogeneity in communities and ecosystem functions. These termites influence the local availability of nutrients in part by redistributing nutrients across the landscape, but the links between termite ecosystem engineering and the soil microbes that are the metabolic agents of nutrient cycling are little understood. We used DNA metabarcoding of soils from Odontotermes montanus mounds to examine the influence of termites on soil microbial communities in a semi‐arid Kenyan savanna. We found that bacterial and fungal communities were compositionally distinct in termite‐mound topsoils relative to the surrounding savanna, and that bacterial communities were more diverse on mounds. The higher microbial alpha and beta diversity associated with mounds created striking spatial patterning in microbial community composition, and boosted landscape‐scale microbial richness and diversity. Selected enzyme assays revealed consistent differences in potential enzymatic activity, suggesting links between termite‐induced heterogeneity in microbial community composition and the spatial distribution of ecosystem functions. We conducted a large‐scale field experiment in which we attempted to simulate termites’ effects on microbes by fertilizing mound‐sized patches; this altered both bacterial and fungal communities, but in a different way than natural mounds. Elevated levels of inorganic nitrogen, phosphorus and potassium may help to explain the distinctive fungal communities in termite‐mound soils, but cannot account for the distinctive bacterial communities associated with mounds.

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Effect of low-level flow and Andes mountain on the tropical and mid-latitude precipitating cloud systems: GPM observations - Shailendra Kumar; Aldo S. Moya-Álvarez; Carlos Del Castillo-Velarde; Daniel Martinez-Castro; Yamina Silva (Theoretical and Applied Climatology, 2020)

Differential production of insulin-like growth factor-binding proteins in liver fibrosis progression - Moisés Martínez-Castillo; Dorothy Rosique-Oramas; Zaira Medina-Avila; José Luis Pérez-Hernández; Fatima Higuera-De la Tijera; Daniel Santana-Vargas; Eduardo Esteban Montalvo-Jave; Francico Sanchez-Avila; Aldo Torre; David Kershenobich; Gabriela Gutierrez-Reyes (Molecular and Cellular Biochemistry, 2020)

Genomic data reveal international lineages of critical priority Escherichia coli harbouring wide resistome in Andean condors ( Vultur gryphus Linnaeus, 1758) - Danny Fuentes‐Castillo; Fernanda Esposito; Brenda Cardoso; Gislaine Dalazen; Quézia Moura; Bruna Fuga; Herrison Fontana; Louise Cerdeira; Milena Dropa; Jürgen Rottmann; Daniel González‐Acuña; José L. Catão‐Dias; et al. (Molecular Ecology, 2020)
Critical priority pathogens have globally disseminated beyond clinical settings, thereby threatening wildlife. Andean Condors ( Vultur gryphus ) are essential for ecosystem health and functioning, but their populations are globally near threatened and declining due to anthropogenic activities. During a microbiological and genomic surveillance study of critical priority antibiotic‐resistant pathogens, we identified pandemic lineages of multidrug‐resistant extended‐spectrum β‐lactamase (ESBL)‐producing Escherichia coli colonizing Andean Condors admitted at two wildlife rehabilitation centres in South America. Genomic analysis revealed the presence of genes encoding resistance to hospital and healthcare agents among international E. coli clones belonging to sequence types (STs) ST162, ST602, ST1196 and ST1485. In this regard, the resistome included genes conferring resistance to clinically important cephalosporins (i.e., CTX‐M‐14, CTX‐M‐55 and CTX‐M‐65 ESBL genes), heavy metals (arsenic, mercury, lead, cadmium, copper, silver), pesticides (glyphosate) and domestic/hospital disinfectants, suggesting a link with anthropogenic environmental pollution. On the other hand, the presence of virulence factors, including the astA gene associated with outbreak of childhood diarrhoea and extra‐intestinal disease in animals, was identified, whereas virulent behaviour was confirmed using the Galleria mellonella infection model. E. coli ST162, ST602, ST1196 and ST1485 have been previously identified in humans and food‐producing animals worldwide, indicating that a wide resistome could contribute to rapid adaptation and dissemination of these clones at the human–animal–environment interface. Therefore, these results highlight that Andean Condors have been colonized by critical priority pathogens, becoming potential environmental reservoirs and/or vectors for dissemination of virulent and antimicrobial‐resistant bacteria and/or their genes, in associated ecosystems and wildlife.

Expression dynamics of autophagy-related genes in the cattle tick Rhipicephalus microplus during embryonic development and under increasing larval starvation - Celia González Castillo; Daniel Ortuño Sahagún; Moisés Martínez Velázquez (Experimental and Applied Acarology, 2019)

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

Neuroprotective effect of Mayan medicinal plant extracts against glutamate-induced toxicity - Cristina M. Castillo-Bautista; Luis W. Torres-Tapia; Jorge A. Rangel-Méndez; Sergio R. Peraza-Sánchez; Daniel Cortés; Iván Velasco; Rosa E. Moo-Puc (Journal of Natural Medicines, 2019)

Is Indonesian peatland loss a cautionary tale for Peru? A two-country comparison of the magnitude and causes of tropical peatland degradation - Erik Lilleskov; Kevin McCullough; Kristell Hergoualc’h; Dennis del Castillo Torres; Rodney Chimner; Daniel Murdiyarso; Randy Kolka; Laura Bourgeau-Chavez; John Hribljan; Jhon del Aguila Pasquel; Craig Wayson (Mitigation and Adaptation Strategies for Global Change, 2019)

Morphological diversity of Huaya India fruits (Melicoccus oliviformis Kunth) in the Maya Lowlands - Mónica I. Jiménez-Rojas; Jaime Martínez-Castillo; Daniel Potter; Gabriel R. Dzib; Horacio S. Ballina-Gómez; Luis Latournerie-Moreno; Rubén H. Andueza-Noh (Genetic Resources and Crop Evolution, 2019)

A major locus for resistance to Botryosphaeria dothidea in Prunus - Daniel Mancero-Castillo; Thomas G. Beckman; Philip F. Harmon; José X. Chaparro (Tree Genetics & Genomes, 2018)

Differential Expression of Ion Channels in Adult and Neonatal Rat Ventral Respiratory Column - Celia González-Castillo; Elizabeth Muñoz-Ortiz; Carolina Guzmán-Brambila; Argelia E. Rojas-Mayorquín; Luis Beltran-Parrazal; Daniel Ortuño-Sahagún; Consuelo Morgado-Valle (Journal of Molecular Neuroscience, 2018)

Variability in sensory attributes in common bean (Phaseolus vulgaris L.): a first survey in the Iberian secondary diversity center - Ana Rivera; Daniel Fenero; Antoni Almirall; Juan José Ferreira; Joan Simó; Marçal Plans; Roser Romero del Castillo; Francesc Casañas (Genetic Resources and Crop Evolution, 2013)

Draft whole genome sequence of the cyanide‐degrading bacterium P seudomonas pseudoalcaligenes CECT 5344 - Víctor M. Luque‐Almagro; Felipe Acera; Ma Isabel Igeño; Daniel Wibberg; Ma Dolores Roldán; Lara P. Sáez; Magdalena Hennig; Alberto Quesada; Ma José Huertas; Jochen Blom; Faustino Merchán; Ma Paz Escribano; et al. (Environmental Microbiology, 2013)
Summary P seudomonas pseudoalcaligenes CECT 5344 is a Gram‐negative bacterium able to tolerate cyanide and to use it as the sole nitrogen source. We report here the first draft of the whole genome sequence of a P . pseudoalcaligenes strain that assimilates cyanide. Three aspects are specially emphasized in this manuscript. First, some generalities of the genome are shown and discussed in the context of other P seudomonadaceae genomes, including genome size, G + C content, core genome and singletons among other features. Second, the genome is analysed in the context of cyanide metabolism, describing genes probably involved in cyanide assimilation, like those encoding nitrilases, and genes related to cyanide resistance, like the cio genes encoding the cyanide insensitive oxidases. Finally, the presence of genes probably involved in other processes with a great biotechnological potential like production of bioplastics and biodegradation of pollutants also is discussed.

Regional integration and local change: road paving, community connectivity, and social–ecological resilience in a tri-national frontier, southwestern Amazonia - Stephen G. Perz; Liliana Cabrera; Lucas Araújo Carvalho; Jorge Castillo; Rosmery Chacacanta; Rosa E. Cossio; Yeni Franco Solano; Jeffrey Hoelle; Leonor Mercedes Perales; Israel Puerta; Daniel Rojas Céspedes; Ioav Rojas Camacho; et al. (Regional Environmental Change, 2012)

Cardiac Tissue Injury Resistance During Myocardial Infarction at Adulthood by Developmental Exposure to Cadmium - Ramiro Zepeda; Paula Castillo; Daniel Sáez; Miguel N. Llanos; Ana M. Ronco (Cardiovascular Toxicology, 2012)

Cadmium, copper, lead, and zinc in Mugil cephalus from seven coastal lagoons of NW Mexico - Martin G. Frías-Espericueta; J. Isidro Osuna-López; Martha A. Jiménez-Vega; Daniel Castillo-Bueso; Maria D. Muy-Rangel; Werner Rubio-Carrasco; Gabriel López-López; Gildardo Izaguirre-Fierro; Domenico Voltolina (Environmental Monitoring and Assessment, 2011)

Analysis and Contrast of Different Pervious Pavements for Management of Storm-Water in a Parking Area in Northern Spain - Elena Gomez-Ullate; Elena Castillo-Lopez; Daniel Castro-Fresno; Joseba Rodriguez Bayon (Water Resources Management, 2011)

High compatibility between arbuscular mycorrhizal fungal communities and seedlings of different land use types in a tropical dry ecosystem - Mayra E. Gavito; Daniel Pérez-Castillo; César F. González-Monterrubio; Teresa Vieyra-Hernández; Miguel Martínez-Trujillo (Mycorrhiza, 2008)

A novel KCNQ4 pore-region mutation (p.G296S) causes deafness by impairing cell-surface channel expression - Ángeles Mencía; Daniel González-Nieto; Silvia Modamio-Høybjør; Ainhoa Etxeberría; Gracia Aránguez; Nieves Salvador; Ignacio del Castillo; Álvaro Villarroel; Felipe Moreno; Luis Barrio; Miguel Ángel Moreno-Pelayo (Human Genetics, 2008)

The effect of large‐scale circulation on precipitation and streamflow in the Gulf of California continental watershed - Luis Brito‐Castillo; Arthur V. Douglas; Amando Leyva‐Contreras; Daniel Lluch‐Belda (International Journal of Climatology, 2003)
The interannual variability of summer and winter rainfall and streamflow in the Gulf of California continental watershed is compared. Varimax‐rotated empirical orthogonal function (EOF) analysis is applied to 15 streamflow series, in the period from 1960 to 1990, and two regions are defined: a central region and a southern region. Results show that in both regions, between 1944 and 1999, the long‐term rainfall variability is well explained by the long‐term streamflow variability in both seasons, the result being statistically significant at the 95% level. We conclude that regional streamflows in that period are climate driven. This conclusion is reinforced when we show that the large‐scale circulation (700 hPa heights) explains: (i) wet and dry conditions in both regions; (ii) conditions of wet and dry years with the same signal of El Niño and La Niña events; and (iii) long‐term periods in association with the Pacific decadal oscillation (PDO). When the PDO is in its warm phase, summers are likely to be dry with an El Niño event and wet with a La Niña event. In the cool phase of the PDO, summers are influenced by more localized events (i.e. the position of the subtropical continental ridge). In winter, warm and cool phases of the PDO are likely to be associated with wet and dry winters respectively. Copyright © 2003 Royal Meteorological Society